Analisis Penerapan Prosedur Pembiayaan Gadai Emas di BSI KCP Medan Padang Bulan - Diajeng Regita Nandani (Universitas 45 Surabaya, 2024)
The aim of this research is gold pawn financing, a financing option with gold security attached to a contract that sharia banks provide for production and consumption. Rahn, the collateral will be safeguarded by the bank. a specific amount of time. In this research, the research approach applied is qualitative. Qualitative research is described as research that is postpositivist in orientation and takes place in a natural environment. In this research, the descriptive approach is a data analysis technique that is carried out by summarizing or explaining data without trying to generalize it. This kind of study is known as field research, which is studies that are thorough, factual and descriptive in accordance with the problems raised. explain precisely the circumstances, nature and relationships between the phenomena studied. Considering that the selling price of gold is still relatively high, gold can offer generally constant value and the possibility of future income. Customers who try to pawn (rahn) gold are driven by several needs. Before paying a minimum of 50% of the gold price and as much as 85% to 90% of the bank's assessed gold price, the Islamic bank, which acts as a gold buyer, will evaluate the value of the customer's gold.